2019
DOI: 10.3390/medicina55110713
|View full text |Cite
|
Sign up to set email alerts
|

Technical Factors Affecting Ultrasound Breast Tumor Size as Correlated with Pathological Type

Abstract: Background and Objectives: Accurate breast tumor sizing is very important in treatment planning; as a result, ultrasound (US) plays an important role in diagnosing breast masses, due to its non-magnified image and its availability. The continuous change in the disease pathogenesis of breast cancer and tremendous advances in US imaging technology require the continuous evaluation of this imaging modality. In this study, our aim was to determine the accuracy of US in measuring the size of breast mass, and if the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
(27 reference statements)
0
2
0
Order By: Relevance
“…Importantly, ultrasound has been shown to be accurate, especially in the assessment of tumor size which is the most important indicator for evaluating response (16)(17)(18). Many previous studies have demonstrated only minor differences in tumor size between ultrasound and pathological measurement, which are attributed to unclear margins, edge perception and histological features (19,20). Therefore, change in the largest diameter measured by breast ultrasound is one of the most commonly used clinical formats to balance generalizability and accuracy when assessing clinical response to NAC.…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, ultrasound has been shown to be accurate, especially in the assessment of tumor size which is the most important indicator for evaluating response (16)(17)(18). Many previous studies have demonstrated only minor differences in tumor size between ultrasound and pathological measurement, which are attributed to unclear margins, edge perception and histological features (19,20). Therefore, change in the largest diameter measured by breast ultrasound is one of the most commonly used clinical formats to balance generalizability and accuracy when assessing clinical response to NAC.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, high‐resolution ultrasound (US) and magnetic resonance imaging (MRI) have been strongly incorporated in managing breast lesions. Although MRI has a high sensitivity, it has low specificity for breast lesions, and it also tends to overestimate lesion size 4 . Previous research has indicated that contrast‐enhanced ultrasound (CEUS) may be beneficial in distinguishing malignant breast lesions from benign ones 5 .…”
mentioning
confidence: 99%
“…Although MRI has a high sensitivity, it has low specificity for breast lesions, and it also tends to overestimate lesion size. 4 Previous research has indicated that contrast-enhanced ultrasound (CEUS) may be beneficial in distinguishing malignant breast lesions from benign ones. 5 The diverse CEUS enhancement patterns observed across different breast tumor regions can be primarily attributed to variations in blood perfusion.…”
mentioning
confidence: 99%
“…Conversely, the difference in acoustic impedance at the interface of the adipose and adjacent tissues can be captured using ultrasound imaging; hence, ultrasound examination can aid in the better visualization of adipose tissues [ 7 ]. Moreover, ultrasound aids in accurately depicting lesions [ 16 ]. These findings suggest that ultrasound examination may facilitate an accurate depiction of adipose tissues on the longitudinal sections of neck fat at the dorsal nuchal ligament and HSCN lesions.…”
mentioning
confidence: 99%